2002
DOI: 10.1590/s0006-87052002000300003
|View full text |Cite
|
Sign up to set email alerts
|

Análise dialélica e heterose de populações de milho-pipoca

Abstract: RESUMORealizaram-se cruzamentos dialélicos entre nove populações de milho-pipoca (Zea mays L.) -UNB-2, RS-20, UEM-J1, UEM-M2, CMS-42, CMS-43, Viçosa, Beija-flor e a geração avançada do híbrido triplo Zélia -para a obtenção dos 36 híbridos F 1's a fim de alcançar informação dos valores da capacidade combinatória e heterose. Essas populações e os F 1's foram avaliados em ensaios, em dois anos agrícolas (98/99 e 99/00), em Iguatemi (PR), com três repetições por ano. Os resultados permitiram recomendar compostos f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0
12

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 7 publications
6
27
0
12
Order By: Relevance
“…Larish and Brewbaker (1999) observed negative heterosis in popping expansion, and in some crosses, this trait was less than half of that of the parents. Scapim et al (2002) also found bi-directional dominance. Simon et al (2004) only found positive and zero dominance.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Larish and Brewbaker (1999) observed negative heterosis in popping expansion, and in some crosses, this trait was less than half of that of the parents. Scapim et al (2002) also found bi-directional dominance. Simon et al (2004) only found positive and zero dominance.…”
Section: Resultsmentioning
confidence: 85%
“…ping expansion is a character that can be exploited efficiently in recurrent selection programs. For the production of hybrids, selection based on popping expansion is also recommended during development of lines because, in general, heterosis is null or bidirectional with a low magnitude (Scapim et al, 2002). Following the same idea, selecting for popping expansion is also recommended to be applied in the base population.…”
Section: Resultsmentioning
confidence: 99%
“…Os coeficientes de variação experimental (CV%) foram inferiores a 25%, em relação à produtividade e 16% quanto à capacidade de expansão, o que revela aceitável precisão nos experimentos de campo. Esses valores são próximos aos encontrados por CarpentieriPípolo et al (2002) e Scapim et al (2002).…”
Section: Resultsunclassified
“…Apesar de a pipoca ser altamente apreciada no país e a produção de grãos, uma atividade altamente rentável -comparado ao milho comum, o valor comercial do milho-pipoca é três vezes superior -há poucos programas de melhoramento implementados no Brasil para o lançamento de variedades e híbridos (SAWAZAKI, 1995;PACHECO et al, 1998;SAWAZAKI, 2001;SCAPIM et al, 2002).…”
Section: Introductionunclassified